Grammar explorer - Mackey, Daphne (National Geographic Learning, Cengage Learning, 2015)
Prepares students for academic success through National Geographic content and assignments that mirror the requirements of academic life. Going beyond clear grammar charts and instruction, this book challenges students to think critically while using grammar in their listening, speaking, reading, and writing.